Beyond the matrix: Repository services for qualitative data. (December 2016) - Karcher, Sebastian; Kirilova, Dessislava; Weber, Nicholas
The Qualitative Data Repository (QDR) provides infrastructure and guidance for the sharing and reuse of digital data used in qualitative and multi-method social inquiry. In this paper we describe some of the repository's early experiences providing services developed specifically for the curation of qualitative research data. We focus on QDR's efforts to address two key challenges for qualitative data sharing. The first challenge concerns constraints on data sharing in order to protect human participants and their identities and to comply with copyright laws. The second set of challenges addresses the unique characteristics of qualitative data and their relationship to the published text. We describe a novel method of annotating scholarly publications, resulting in a "transparency appendix" that allows the sharing of such "granular data" (Moravcsik et al., 2013). We conclude by describing the future directions of QDR's services for qualitative data archiving, sharing, and reuse.